2003
DOI: 10.1080/0887044031000062197
|View full text |Cite
|
Sign up to set email alerts
|

Is Optimism Sensitive to the Stressors of Chronic Disease? The Impact of Type 1 Diabetes Mellitus and Multiple Sclerosis on Optimistic Beliefs

Abstract: The aim of the present study was to investigate longitudinally the sensitivity of optimistic beliefs (positive outcome expectancies, efficacy expectancies, and optimistic bias) to disease-related stress (measured by disease duration, depressive symptoms, physical symptoms, physical impairment, and life-events) in Type 1 diabetes (n ¼ 90) and multiple sclerosis (n ¼ 90). First, we examined whether chronically ill patients were less optimistic than a healthy control group (n ¼ 60), which showed that patients rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 79 publications
1
10
0
Order By: Relevance
“…A possible explanation for this may relate to the different conceptualizations of optimism in the literature [48]. According to Fournier et al [49,50], there are at least three different concepts of optimism, namely positive outcome expectancies, positive efficacy expectancies, and optimistic bias, which were found to react differently to chronic disease depending on their differential sensitivity to disease-related stressors [51]. Thus, it might be that the LOT scale was not sensitive enough to those concepts, or perhaps a more specific measure of optimism is needed regarding epilepsy, as was suggested recently by Pais-Ribeiro et al [52].…”
Section: Discussionmentioning
confidence: 89%
“…A possible explanation for this may relate to the different conceptualizations of optimism in the literature [48]. According to Fournier et al [49,50], there are at least three different concepts of optimism, namely positive outcome expectancies, positive efficacy expectancies, and optimistic bias, which were found to react differently to chronic disease depending on their differential sensitivity to disease-related stressors [51]. Thus, it might be that the LOT scale was not sensitive enough to those concepts, or perhaps a more specific measure of optimism is needed regarding epilepsy, as was suggested recently by Pais-Ribeiro et al [52].…”
Section: Discussionmentioning
confidence: 89%
“…Finally we should mention that dispositional optimism is thought to be a fairly stable personality characteristic (Scheier and Carver 1985) but the fact that it has been found to be associated with social desirability and anxiety (Schweizer et al 1999), depression (Fournier et al 2003) and to have a mediating role between pain and QOL (Wong and Fielding 2007), suggests that it may not be completely stable, in which case we may be assessing an aspect of anxiety or depression and/or similar constructs.…”
Section: Discussionmentioning
confidence: 96%
“…Finally, since research shows that depression is a risk factor for optimistic beliefs (Fournier et al 2003), it appears relevant to diagnose and treat depression of people with chronic pain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study by Pakenham and Cox (2009) showed that significant gains in vital and spiritual resources can occur in patients diagnosed with multiple sclerosis over the course of time, while Fournier, de Ridder, and Bensing (2003) indicate that an optimistic attitude an plays an important role. Vital resources are perceived as more important, probably because these resources had been lost or significantly limited earlier.…”
Section: Significance Of Vital and Spiritual Resources In Patientsmentioning
confidence: 99%